Principles of Qur’anic Exegesis (Usul Tafsir): a historical background - Fadzil, Ammar (2021)
Understanding the message of the Qur‟an is one of the most significant purpose of the revelation of the Qur‟an. To achieve it, certain principles are needed such as the knowledge of principles of Qur‟anic exegesis, the Arabic team of which is usul tafsir. This article, therefore, seeks to discuss the definition of usul tafsir, its historical development and a review of some selected writings in this field. The methodology employed is a content analysis to analyze the collected data to arrive at the vivid findings.